2011
DOI: 10.1097/paf.0b013e3182186d5d
|View full text |Cite
|
Sign up to set email alerts
|

Survival of Anesthetized Sus scrofa After Cycling (7-Second On/3-Second Off) Exposures to an Electronic Control Device for 3 Minutes

Abstract: Electronic control devices (ECDs) may eventually be deployed by the military in a manner resulting in longer exposures than those encountered during law-enforcement operations. In a previous study, 18 repeated cycling (5-second on/5-second off) exposures (within a 3-minute period) of anesthetized swine to an ECD (TASER International's Advanced TASER X26 device) resulted in leg muscle contraction, acidosis, and increases in blood electrolytes. In the current study, experiments were performed to examine effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(62 citation statements)
references
References 21 publications
6
56
0
Order By: Relevance
“…Both respiratory and metabolic changes could contribute to acidosis. In the experiments of Jauchem et al, 4,30,33 even if respiratory effects could have been alleviated (e.g., by mechanical ventilation), it is likely that acidosis would have still been present, as reflected by the high levels of lactate. In addition, Tohdoh et al 82 reported that excessive muscle contraction, in some instances, could induce both metabolic and respiratory acidosis.…”
Section: Acidosis and Blood Lactatementioning
confidence: 99%
See 4 more Smart Citations
“…Both respiratory and metabolic changes could contribute to acidosis. In the experiments of Jauchem et al, 4,30,33 even if respiratory effects could have been alleviated (e.g., by mechanical ventilation), it is likely that acidosis would have still been present, as reflected by the high levels of lactate. In addition, Tohdoh et al 82 reported that excessive muscle contraction, in some instances, could induce both metabolic and respiratory acidosis.…”
Section: Acidosis and Blood Lactatementioning
confidence: 99%
“…It is not known, however, whether that particular ECD can cause incapacitating muscle contractions. In the experiments of Jauchem et al, 4,30,33 blood lactate was the one factor that exhibited the greatest consistent change dependent on the relative amount of ECD exposure. Bozzuto 79 noted that physical exertion alone can result in severe hyperlactacidaemia.…”
Section: Acidosis and Blood Lactatementioning
confidence: 99%
See 3 more Smart Citations